A review of the experience of childhood hepatitis A vaccination in Saudi Arabia and Turkey: implications for hepatitis A control and prevention in the Middle East and North African region - Selim Badur; Serdar Öztürk; Alev Ozakay; Mansour Khalaf; Debasish Saha; Pierre Van Damme (Taylor & Francis Group, 2021)
In most countries of the Middle East and Northern African (MENA) region, a high hepatitis A virus (HAV) endemicity has been documented. Few others, such as Saudi Arabia and Turkey, are transitioning from high to intermediate endemicity. There is a paucity of recently published HAV disease burden that could be useful to inform or strengthen relevant national hepatitis A vaccination policy and other prevention strategies in the region. This review summarizes information on HAV epidemiology before and after the implementation of a childhood hepatitis A vaccination program in Saudi Arabia and Turkey. In both countries, a clear shift in the age of first HAV exposure has been documented, with more homogeneous trends across regions in Saudi Arabia compared to Turkey. Utilizing the experience of Saudi Arabia and Turkey with hepatitis A vaccination, countries in the region are encouraged to foster discussions on potential vaccination strategies suitable for their own setting.